Activation of Sugarcane Bagasse Biosorbent with Potassium Hydroxide and Hydrogen Chloride to Reduce Color of Batik Wastewater - Pramitasari, Noven; Ramadani, Faisal Basri; Azis, Rovy Agustian; Bezariani, Calista Safa; Berliana, Rohinoor Intan; Badriani, Ririn Endah; Kartini, Audiananti Meganandi; Fildzah, Cantika Almas (Jurnal Rekayasa Kimia & Lingkungan, 2024)
The textile industry, particularly the batik sector, significantly contributes to the Gross Domestic Product (GDP) of East Java Province. However, the batik dyeing process, which uses synthetic dyes like remazol, rapid, and naphthol, causes environmental issues due to the non-biodegradable nature of these dyes, leading to environmental pollution such as an increase in color levels in water bodies. This research investigated using activated sugarcane bagasse with KOH and HCl in batch adsorption systems as an alternative method. It compared the color efficiency removal in batik wastewater with variation biosorbent mass, contact time, and activator type. The study found that the highest percentage removal of dye substances was achieved with the KOH-activated biosorbent, reaching 69.46%, and the HCl-activated biosorbent demonstrated a 60.98% removal efficiency with a mass variation of 0.4 grams and a contact time of 30 minutes. Statistical analysis using multiple linear regression showed that independent variables (biosorbent mass, contact time, and activator) significantly affect the dependent variable (color removal efficiency) simultaneously. In the partial test, the independent variables of biosorbent mass and type of activator significantly affect color removal efficiency, but contact time does not significantly affect color removal efficiency.